The Impact of Empowering Pisang Mas Banana Farmers through Partnership with PT. Great Giant Pineapple - Nela Sara Gratia Simanjuntak; Indra Lestari Fawzi (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2021)
Until now, farmers’ welfare has not been given much attention. It can be seen from the fact that a lot of farmers have low income, and a lack of skills and knowledge. One of the ways to improve farmer welfare is to empower farmers, as done by PT. Great Giant Pineapple in Lampung, which has formed a partnership with farmers groups in Tanggamus Regency. This research is aimed to analyze the impact of empowering pisang mas (some type of ladyfinger) banana farmers, through a partnership with the company based on the concept of CSV (Creating Shared Value). This study used a qualitative method, and the informants were selected using the purposive sampling technique. Data were collected through in-depth interviews and observations, as well as document studies. The informants consisted of banana farmers who are members of farmers groups, as well as group leaders, the farmers’ cooperative management, and the CSV staff. The results of the study indicate that the impact of the partnership program between farmers groups and PT. Great Giant Pineapple can be grouped into economic and social impacts. On the economic side, the impact can be seen in the improvement of farmers’ business skills, increase in farmers’ income, more job opportunities for the surrounding community, and farmers’ access to other institutions. Meanwhile, the social impacts include increase in capacities, skills as well as motivation and confident behavior among farmers, and the strengthening capacities among the farmers groups.